Hygiene dan Sanitasi Pengelolaan Makanan di Instalasi Gizi RS X Depok - Nandya, Lita; Nina, Nina (2-TRIK: TUNAS-TUNAS RISET KESEHATAN, 2022)
Hygiene and sanitation in food management is included in the implementation of food health, namely monitoring, controlling and increasing the level of food hygiene and sanitation. This study aims to evaluate food management hygiene and sanitation at the Nutrition Installation of X Depok Hospital in accordance with the standards of the Minister of Health of the Republic of Indonesia Number 7 of 2019. This research uses a qualitative approach involving the head of nutrition, processors, waiters and supporting information from health workers environment. Data collection techniques were obtained through observation, interviews and document review. The results showed that food management hygiene and sanitation were in accordance with the standards set by the government, but it was found that for food handlers, there were 2 inappropriate indicators, namely health checks which were carried out once a year and discipline in using masks; for good manufacturing practice, there is 1 indicator that is not suitable, namely the transportation of food that has not used a trolley with temperature control; and for food control, there is 1 indicator that is not appropriate, namely internal control, where health checks for handlers have not been carried out twice a year.Keywords: sanitary hygiene; nutrition installation; foodABSTRAK Hygiene dan sanitasi pengelolaan makanan termasuk dalam penyelenggaraan kesehatan makanan yaitu pengawasan, pengendalian serta peningkatan taraf hygiene dan sanitasi makanan. Penelitian ini memiliki tujuan untuk melakukan evaluasi tentang hygiene dan sanitasi pengelolaan makanan di Instalasi Gizi RS X Depok sesuai dengan standar Peraturan Menteri Kesehatan Republik Indonesia Nomor 7 Tahun 2019. Penelitian ini menggunakan pendekatan kualitatif yang melibatkan kepala gizi, pengolah, pramusaji dan informasi pendukung petugas kesehatan lingkungan. Teknik pengumpulan data diperoleh melalui observasi, wawancara dan telaah dokumen. Hasil penelitian menunjukkan bahwa hygiene dan sanitasi pengelolaan makanan sudah sesuai dengan standar yang ditetapkan oleh pemerintah, namun  ditemukan bahwa untuk penjamah makanan, terdapat 2 indikator tidak sesuai yaitu cek kesehatan yang dilaksanakan sekali dalam setahun dan kedisiplinan penggunaan masker; untuk good manufacturing practice, ada 1 indikator yang tidak sesuai yaitu pengangkutan makanan yang belum menggunakan troli dengan pengatur suhu; dan untuk pengawasan makanan, ada 1 indikator yang tidak sesuai yaitu pengawasan internal, dimana cek kesehatan penjamah belum dilaksanakan dua kali dalam setahun.Kata kunci: hygiene sanitasi; instalasi gizi; makanan